The Role of Parenting in the Use of Gadgets in Early Childhood: A Case Study of RA An-Najah I Karduluk Sumenep - Moh. Abdan Syakuro; Raden Rachmy Diana; Ardhana Reswari; Danang Prastyo; Imalah (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The importance of parenting in the use of gadgets is the main point for optimizing children's growth and development in accordance with the standard for early childhood learning achievement levels (STPPA). This study aims to describe the role of parenting in the use of gadgets in early childhood: a case study of RA An-Najah I Karduluk Sumenep which is described through a qualitative approach. The subjects of this study were teachers, parents, and students of RA An-Najah I. The data collection techniques used were the results of interviews, observations, and documentation in the use of early childhood gadgets at RA An-Najah I. The data analysis used was analysis. non-statistical. The results of the research are that some parents of RA An-Najah I students apply permissive parenting to their children, which is freeing children's activities with low control so that children's freedom is very high. On the other hand, parents also apply the pattern of guidance by setting limits on how long they play gadgets for children, providing rules for accessing the features contained in the device, and accompanying children directly when playing on the device as well as directing children to access the features in it.